Sistem Informasi Pemetaan Warisan Budaya Kawasan Banten Lama Berbasis Android - Ery Dewayani; Chairisni Lubis; Bagus Mulyawan (Faculty of Information Technology, Universitas Tarumanagara, 2019)
In this global era, when seeking information or communicate with each other, people are using information technology to support those activities. Smartphones for example, is one of affordable technology that can be owned by common people. These days, people are using smartphones anywhere and any time. On every smartphones that being used, it has a operating systems to manages smartphones hardware and provide services that given. Android is the most popular of a mobile operating systems that being used to operate smartphones in the world. Through the popularity of android and growing smartphones users, transmitting information are more effective if the information can be accessed using smartphones. On the first year of research” Mapping Banten Lama’s Cultural Heritage Website “has already developed, and to make accessibility of the information more convenient, on the second year of research has developed application program “Android Based Information System for Mapping Banten Lama’s Cultural Heritage”. This application program is accessible through any kind of android smartphones. Prototyping method is used to develop this application program. For storing data, this application program use MySql database that operate inside server (hosting) so it can can be accessed through internet. Android studio and Java programming language are used to build this application program. Black Box Testing and User Acceptance Test (UAT) are used to test this application program. The result of this research is develop a product of software that can be accessed through android smartphones. Pada era global saat ini masyarakat menggunakan teknologi informasi dalam mencari informasi maupun untuk berkomunikasi. Salah satu teknologi yang terjangkau dan dapat dimiliki oleh masyarakat umum adalah handphone. Mereka membawa dan menggunakan handphone setiap saat dimanapun mereka berada. Perusahaan gadget mulai mengembangkan perangkatnya menggunakan sistem operasi Android yang akhir-akhir ini sangat popular dan menjadi perhatian masyarakat Indonesia maupun dunia. Dengan memanfaatkan perkembangan teknologi tersebut, dalam mengenalkan berbagai informasi kepada masyarakat umum akan lebih efektif bila informasi dapat diakses melalui handphone. Website Warisan Budaya Kawasan Banten Lama sudah dibuat pada penelitian tahun pertama dan agar lebih memudahkan masyarakat luas untuk akses , pada penelitian tahun kedua dikembangkan suatu program aplikasi “Sistem Informasi Pemetaan Warisan Budaya Kawasan Banten Lama Berbasis Android”. Program aplikasi yang dikembangkan ini dapat diakses diberbagai tipe handphone yang berbasis Android. Metodologi pengembangan sistem menggunankan metode Prototyping. Basisdata menggunakan My Sql, yang disimpan dalam server (hosting) agar dapat diakses melalui internet. Selain itu program aplikasi menggunakan Android Studio dengan bahasa pemrograman Java. Metode pengujian menggunakan User Acceptance Test (UAT). Penelitian ini menghasilkan produk software yang dapat diakses melalui handphone berbasis android.